Sin3a-associated Hdac1 and Hdac2 are essential for hematopoietic stem cell homeostasis and contribute differentially to hematopoiesis - Heideman, M. R.; Lancini, C.; Proost, N.; Yanover, E.; Jacobs, H.; Dannenberg, J.-H. (Haematologica (Roma), 2014)
Class I histone deacetylases are critical regulators of gene transcription by erasing lysine acetylation. Targeting histone deacetylases using relative non-specific small molecule inhibitors is of major interest in the treatment of cancer, neurological disorders and acquired immune deficiency syndrome. Harnessing the therapeutic potential of histone deacetylase inhibitors requires full knowledge of individual histone deacetylases in vivo. As hematologic malignancies show increased sensitivity towards histone deacetylase inhibitors we targeted deletion of class I Hdac1 and Hdac2 to hematopoietic cell lineages. Here, we show that Hdac1 and Hdac2 together control hematopoietic stem cell homeostasis, in a cell-autonomous fashion. Simultaneous loss of Hdac1 and Hdac2 resulted in loss of hematopoietic stem cells and consequently bone marrow failure. Bone-marrow-specific deletion of Sin3a, a major Hdac1/2 co-repressor, phenocopied loss of Hdac1 and Hdac2 indicating that Sin3a-associated HDAC1/2-activity is essential for hematopoietic stem cell homeostasis. Although Hdac1 and Hdac2 show compensatory and overlapping functions in hematopoiesis, mice expressing mono-allelic Hdac1 or Hdac2 revealed that Hdac1 and Hdac2 contribute differently to the development of specific hematopoietic lineages.